A resilient Asia amidst global financial crisis : from crisis management to global leadership - Kohli, Harinder S. 1945-; Sharma, Ashok 1974- (New Delhi SAGE Publications, 2010)
Based on the papers presented and discussions held at a high level Regional Forum organized by the Asian Development Bank in January 2010.
Includes bibliographical references.
Keywords: Finance -- Asia; Global Financial Crisis, 2008-2009.; Asia -- Economic conditions -- 21st century; Asia -- Economic policy -- 21st century